The contemporary echocardiography approach to diagnosis of pulmonary hypertension and non-invasive estimation of pulmonary artery pressure - M.Yu. Kolesnyk (Кардіохірургія та інтервенційна кардіологія)
The review presents the contemporary possibilities of echocardiography in the diagnosis of pulmonary hypertension. The algorithm used to determine probability of the pulmonary hypertension by means of echocardiography based on 2015 ESC guidelines is presented. The technical aspects of the study are described, as well as main formulas used for non-invasive estimation of systolic, average and diastolic pulmonary artery pressure, and their limitations. The possibilities of pulmonary vascular resistance estimation and echocardiographic criteria for differential diagnosis of pre-capillary and post-capillary pulmonary hypertension are discussed.